PENGARUH PELATIHAN REGULASI EMOSI TERHADAP PENGURANGAN STRES DAN PENINGKATAN OPTIMISME PADA PENGANGGUR DI YOGYAKARTA - Karjuniwati, Karjuniwati (Psikoislamedia: Jurnal Psikologi, 2019)
This study aims to determine the influence of emotion regulation training for stress reduction and increased optimism on the unemployed in Yogyakarta, especially the unemployed and a half unemployed. Emotion regulation training is training that uses concepts based on skills Greenberg recognize emotions, emotional expression skills, skills to manage emotions, and skills to change negative emotions into positive emotions. Subjects in this study is the subject of underemployed. The data was collected using a stress scale, an optimism scale, interviews and observation. The research design used was pre-test post-test control group design. Analysis of the research is quantitative and qualitative analysis. Quantitative analysis with hypothesis testing using t-test analysis test to determine whether there is emotion regulation training effect in reducing stress and increasing optimism among the experimental group and control group. Qualitative analysis was conducted based on observation, interview, job sheets. The result of this study is no difference of level of stress and levels of optimism significantly between experimental groups and control groups before training, after training and 2 weeks after training.